A Human Development Index by Internal Migrational Status - Kenneth Harttgen; Stephan Klasen (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2009)
Migration continues to be a very important income diversication strategy, es- pecially for poor populations in developing countries. However, while there has been much analysis on the economic consequences of migration for migrants and the receiving regions, whether internal migration improves or deteriorates human development is not easy to determine. This papers applies a recently de- velopment analytical framework that allows to calculate the HDI for subgroups of a population. We use this approach to calculate the HDI by internal migra- tional status to assess the di®erences between the levels of human development of internal migrants compared to non-migrants, and also across countries as well as by urban and rural areas. An empirical illustration for a sample of 16 low and middle income countries shows that, overall, internal migrants slightly achieve a higher level of human development than non-migrants. The results further show that di®erences in income between migrants and non-migrants are generally higher than di®erences in education and life-expectancy. Disag- gregating the analysis by urban and rural areas reveals that urban internal migrants are better o® than urban non-migrants and rural migrants are better o® than rural non-migrants.
Keywords: 330; Human Development; Migration Income Inequality; Differential Mortality; Inequality in Education